Sejarah Kemunduran Fiqh Dan Masa Kebangkitan Serta Pembaharuan Fiqh - Dinar Mufidah; Zebada Darell Frijatuluah; Muhammad Ata Al Fikri (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
Fiqh studies constitute an essential component in the development of Islamic law, serving as a normative and practical framework to address various issues faced by the Muslim community. This article aims to examine the concept of fiqh and its scope of study in Islam, as well as to analyze its role in responding to social dynamics and contemporary changes. This research employs a qualitative approach using library research methods. The data are derived from the Qur’an, hadith, classical fiqh literature, and relevant contemporary scholarly works on Islamic law. Data analysis is conducted through a descriptive-analytical method to explore the concept of fiqh, its objects of study, and its relevance in modern life. The findings indicate that fiqh functions not merely as a collection of practical legal rulings, but also as a dynamic and contextual instrument of ijtihad. This flexibility enables Islamic law to remain relevant in addressing evolving social, economic, and cultural issues. Therefore, fiqh studies play a strategic role in maintaining harmony between the normative texts of Islamic law and the realities of Muslim life.